MESOCARPO BABAÇU: EFEITO COMO SUPLEMENTO ALIMENTAR DURANTE O TREINAMENTO RESISTIDO. - SOARES, Maísa Carvalho Rezende (2018)
The babassu mesocarp, a product rich in carbohydrates, is widely used by the population, such as food and medicine. It was our aim to evaluate the use of the babassu mesocarp (Attalea speciosa), as a food supplement during resistance training (TR). Males Swiss mice, 60 days of age, 35 to 40 g of weight, were divided into 4 groups (n = 8). Control: untreated and not trained; Babassu (BAE): treated with aqueous extract of babassu mesocarp [(BAE) (25 mg/Kg)], by oral route, five times a week, during eight weeks; Training (TRE): submitted to TR in a steps of a ladder, with progressive weight, and group TREBAE: submitted to TR and treated with BAE. After eight weeks, the animals were killed to the biochemical, immunologic and histologic evaluations. The maximum strength was found in group TRE after the second week. A reduction in the corporal weight, retroperitoneal and interstitial fats deposits and T helper lymphocytes (Th) (TCD4 + CD69 +) was detected after training (TRE and TREBAE). In the Group TREBAE it was detected an increase in AST and ALT concentration and simultaneously a decrease in the triglycerides concentration, followed by a reduction in lymphocytes and macrophages numbers. Supplementation with EAB always reduced cholesterol and the population of activated macrophages, but increased activated B lymphocytes and IL- 6 concentration. When supplementation was associated to TR a decrease in the TNF-α production was observed. We propose the use of babassu mesocarp as a food supplement during exercises, due to its immunomodulatory effect on the lymphocytes and macrophages population, cytokine production and additional effect on the control of circulating concentrations of cholesterol and triglycerides, especially for the treatment of dyslipidemias.